Toleransi Tanaman Akasia (Acacia Mangium Wild.) terhadap Tingkat Salinitas di Pembibitan - Elfarisna Elfarisna; Hermawan Niaga; Rita Tri Puspitasari (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
Acacia is a plant that can be used as the main ingredient of paper making. The potential of acacia wood pulp as the raw material is already widely recognized by the timber industry. Acacia also has potential as a plant greenery in urban areas. Production of acacia plants can be done through the efforts of agricultural extension. Enterprises agricultural extension can be done by expanding the agricultural frontier acacia plants in saline land. The purpose of the study to know acacia plant tolerance to salinity levels in the nursery. The research was conducted from April to July 2013 in the experimental garden of the Faculty of Agriculture, University of Muhammadiyah Jakarta. The research is used Randomized Complete Block Design (RCBD) with five treatments NaCl level concentration, ie P1 Without NaCl/Control, P2 (0.5% concentration) P3 (concentration of 1%), P4 (1.5% concentration) and P5 (concentration of 2%). Parameters measured were percentage growth, plant height, leaf number, stem diameter, plant fresh weight and dry weight of plants. The results showed salinity level significantly affected all parameters observed. A salt concentration of 1% is the maximum saline tolerance conditions for growth acacia.